A Chinese herbs complex ameliorates gut microbiota dysbiosis induced by intermittent cold exposure in female rats - Jin, Lu; Bian, Xiangyu; Dong, Weiyun; Yang, Renren; Jing, Che; Li, Xi; Yang, Danfeng; Guo, Changjiang; Gao, Weina (Frontiers in Microbiology, 2022)
Cold is a common source of stress in the alpine areas of northern China. We found that cold exposure can lead to significant changes in the composition of gut microbiota, which in turn affect intestinal barrier and other physiological functions. In recent years, studies have reported that Chinese herbal extracts and their fermentation broth have a significant effect on gut microbiota. The aim of this study was to study the probiotic effect of a self-designed Chinese herbs complex on the intestinal environment of rats exposed to cold. The rats were treated with intermittent cold exposure and Chinese herbs complex for 14 days, the gut microbiota composition and other parameters were examined. The 16s ribosomal DNA high-throughput sequencing and analysis confirmed that Chinese herbs complex positively improved the gut microbiota. The relative abundance of some probiotics such as Roseburia, Parasutterella and Elusimicrobium in rats treated with Chinese herbs complex were significantly increased. Serum D-LA and LPS were increased in cold exposure group and decreased in Chinese herbs complex-treated group. Moreover, protein expression of intestinal occludin was significantly increased by Chinese herbs complex. In conclusion, Chinese herbs complex is effective in restoring the gut microbiota caused by cold exposure, improve the function of intestinal barrier, and may act as a prebiotic in combatting gut dysbiosis.